Becoming green, becoming leaders: Identity narratives in sustainability leadership development. Issue 1 (February 2018) - Heizmann, Helena; Liu, Helena
Sustainability leadership, exercised towards ecologically sustainable practices in business and society, has emerged as an important aim of leadership development programmes. Through the multimodal discursive analysis of a sustainability leadership centre in Australia, we demonstrate how its identity narratives reproduce individualist ideals of leadership and take for granted the hyperagency of heroic individuals to single-handedly solve environmental crises. Specifically, we illustrate how the development of sustainability leaders is co-constructed through the Buddhist narrative of Prince Siddhartha via three stages: leaders first find their calling that activates their inherent capability to effect change, reach awakening through self-discovery and self-empowerment with the help of the development programme, and finally transform the world through building both successful and meaningful careers. In the light of these findings, we question whether sustainability leadership discourses glorify the self and ironically sustain our disconnection from nature in the pursuit of business success.